Women's lives : - Kirk, Gwyn (McGraw-Hill, 2000)
This interdisciplinary, multicultural text-reader provides an introduction to women's studies within a global context by examining the diversity of women's lives across categories of race-ethnicity, class, sexuality, disability, and age. Substantial chapter introductions provide statistical information and explanations of key concepts and ideas as a context for the reading selections. Each chapter includes reading questions and suggestions for taking action, to help students link what they learn to their own lives and to the world around them.